Sex and base excision repair as key susceptibility factors for alkylation-induced mutations, toxicity and hepatic cancer - Jennifer E. Kay; Joshua J. Corrigan; Lindsay B. Volk; Amanda L. Armijo; Norah A. Owiti; Lee J. Pribyl; Ilana S. Nazari; Dorothea K. Torous; Svetlana L. Avlasevich; Robert G. Croy; Dushan N. Wadduwage; Sebastian E. Carrasco; et al. (DNA Repair, 2026)

The effects of simultaneous isometric and eccentric- or concentric-biased exercise on cardiovascular and muscular health of young individuals - A. W. Baross; B. H. Wright; D. A. Langdon; A. D. Kay; M. Cauchi; A. Clarke; B. Pitham; C. Willmont; T. Barnett; C. Key; M. Reynolds; A. Thomas; et al. (European Journal of Applied Physiology, 2026)

Magnetotelluric constraints on natural hydrogen potential in the southern Gawler Craton, Australia - R. Margiono; R. Daruso; A. Gubina; G. Heinson; S. Constable; B. Kay; G. Boren (Australian Journal of Earth Sciences, 2026)

A Multimedia Arsenic Exposure Assessment for the Hopi Tribe, AZ, USA - Adam C. Carl; Robert A. Canales; Jonathan E. Blohm; Lorencita Joshweseoma; Steven J. Hadeed; Jefferey L. Burgess; Robin B. Harris; Mary Kay O’Rourke (Exposure and Health, 2025)

Reply to Beltaos (2024). Letter to the Editor regarding “Paleofloodscapes: Application of sediment source fingerprinting to track flood regime change over space and time at the Peace-Athabasca Delta, Canada” by Kay et al. (2024), Sci. Total Environ. 912 169538 - Mitchell L. Kay; Lauren A. MacDonald; Johan A. Wiklund; Cory A.M. Girard; Brent B. Wolfe; Roland I. Hall (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

‘Paleofloodscapes’: Application of sediment source fingerprinting to track flood regime change over space and time at the Peace-Athabasca Delta, Canada - Mitchell L. Kay; Lauren A. MacDonald; Johan A. Wiklund; Cory A.M. Girard; Brent B. Wolfe; Roland I. Hall (Science of The Total Environment, 2024)

The multiview observatory for solar terrestrial science (MOST) - N. Gopalswamy; S. Christe; S.F. Fung; Q. Gong; J.R. Gruesbeck; L.K. Jian; S.G. Kanekal; C. Kay; T.A. Kucera; J.E. Leake; L. Li; P. Mӓkelӓ; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Corrigendum to “Quantification of microplastics in sediments from Narragansett Bay, Rhode Island USA using a novel isolation and extraction method” [Mar. Pollut. Bull. 174 (2022) 113254] - Michaela Cashman; Troy Langknecht; Dounia El Khatib; Robert M. Burgess; Thomas B. Boving; Sandra Robinson; James Farnan; Kay T. Ho (Marine Pollution Bulletin, 2023)

Wild lime psyllid Leuronota fagarae Burckhardt (Hemiptera: Psylloidea) picorna-like virus full genome annotation and classification - Douglas S. Stuehler; Wayne B. Hunter; Yisel Carrillo-Tarazona; Hector Espitia; Joseph M. Cicero; Tracey Bell; Hannah R. Mann; Sasha-Kay V. Clarke; Thomson M. Paris; Jackie L. Metz; Tom D'Elia; Jawwad A. Qureshi; et al. (Journal of Invertebrate Pathology, 2023)

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

First evidence of widespread, severe soil erosion underneath centre-pivot irrigation systems - Pedro V.G. Batista; Victor B. da S. Baptista; Florian Wilken; Kay Seufferheld; John N. Quinton; Peter Fiener (Science of The Total Environment, 2023)

Plasma activated water offers food security opportunities by increasing shelf life of freshwater fisheries products in South Africa - Kay Howard; Frederich Henneke; Olivia J. B. Chalwin-Milton; Carel J. Oosthuizen; Peter Johnston; Kirsty L. Bayliss (Food Security, 2023)

Adapting an Undergraduate Summer Internship to a Virtual Format: Implementing a Mentored Cancer Research Experience to Meet Rising Demand for Flexible Learning Environments - Kay See Tan; Richard J. Koppenaal; Shireen Lewis; Colin B. Begg; Mengmeng Du (Journal of Cancer Education, 2023)

Intralesional application of ribavirin in two American flamingos (Phoenicopterus ruber) with poxvirus infection - Giuseppe M Marcello; Kali A Holder; Sara Hallager; Benjamin B Norton; Kay A Backues; Anna E Tyler; Ayo Zeitlin; Evan Murray-Hiteshew; Suzan Murray (Journal of Comparative Pathology, 2023)

Public perception of urban wildlife during a COVID-19 stay-at-home quarantine order in Chicago - Maureen H. Murray; Kaylee A. Byers; Jacqueline Buckley; Elizabeth W. Lehrer; Cria Kay; Mason Fidino; Seth B. Magle; Danielle German (Urban Ecosystems, 2023)

Paleolimnological evaluation of metal(loid) enrichment from oil sands and gold mining operations in northwestern Canada - Mitchell L. Kay; Izabela Jasiak; Wynona H. Klemt; Johan A. Wiklund; Jelle A. Faber; Lauren A. MacDonald; James V.K. Telford; Cory A.M. Savage; Colin A. Cooke; Brent B. Wolfe; Roland I. Hall (Environmental Research, 2023)

The value of individual identification in studies of free-living hyenas and aardwolves - Olivia S. B. Spagnuolo; Marie A. Lemerle; Kay E. Holekamp; Ingrid Wiesel (Mammalian Biology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Plant community responses to experimental climate manipulation in a Welsh ombrotrophic peatland and their palaeoenvironmental context - Luke O. Andrews; James G. Rowson; Simon J. M. Caporn; Nancy B. Dise; Eleanor Barton; Ed Garrett; W. Roland Gehrels; Maria Gehrels; Martin Kay; Richard J. Payne (Global Change Biology, 2022)
We test whether vegetation community composition from a 10‐year climate manipulation experiment on a Welsh peat bog resembles vegetation communities during periods of climate change inferred from a peat core. Experimentally warmed and combined warmed and droughted treatments drove significant increases in ericaceous shrubs but Sphagnum was unaffected. Similarly, Calluna vulgaris seeds increase during inferred warmer periods in the palaeoecological record. Experimental short‐term episodic drought (four 4‐week drought treatments) did not affect vegetation. Plant community composition has undergone several abrupt changes throughout the past c. 1500 years, often in response to human disturbance. Only slight changes occurred during the Medieval Climate Anomaly (c. 950–1250 Common Era [CE]) in vegetation and hydrology, while abrupt changes occurred during the Little Ice Age (c. 1300–1850 CE) when water tables were highest, suggesting that these shifts were driven by changes in water table, modulated by climate. A period of water table drawdown c. 1800, synchronous with historical records of increased drainage, corresponds with the development of the present‐day vegetation community. Modern analogues for fossil material, characterized by abundant Rhynchospora alba and Sphagnum pulchrum , are more common after this event. Vegetation changes due to climate inferred from the palaeo record differ from those observed in the experiments, possibly relating to differences in the importance of drivers of vegetation change over varying timescales. Whereas temperature is frequently identified as the dominant driver of plant community change in experiments, sustained changes in water table appear to be more important in the long‐term record. We find evidence that recent climate change and other anthropogenic stressors (e.g. drainage, heavy metal and nitrogen pollution) may promote the development of novel plant communities without analogues in the fossil record. These communities may be poorer at sequestering carbon and may respond differently to future climate change.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Field testing cellulose-water oxygen isotope relations in periphyton for paleohydrological reconstructions - Cory A. M. Savage; Casey R. Remmer; James V. Telford; Mitchell L. Kay; Eva Mehler; Brent B. Wolfe; Roland I. Hall (Journal of Paleolimnology, 2021)

Inflammation biomarkers associated with arsenic exposure by drinking water and respiratory outcomes in indigenous children from three Yaqui villages in southern Sonora, México - Christian B. Vega-Millán; Ana G. Dévora-Figueroa; Jefferey L. Burgess; Paloma I. Beamer; Melissa Furlong; R. Clark Lantz; Diana Meza-Figueroa; Mary Kay O´Rourke; Leticia García-Rico; Edna R. Meza-Escalante; José J. Balderas-Cortés; Maria M. Meza-Montenegro (Environmental Science and Pollution Research, 2021)

Building upon open-barrel corer and sectioning systems to foster the continuing legacy of John Glew - James V. Telford; Mitchell L. Kay; Harman Vander Heide; Johan A. Wiklund; Tanner J. Owca; Jelle A. Faber; Brent B. Wolfe; Roland I. Hall (Journal of Paleolimnology, 2021)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Method development for rapid quantification of Rn-222 in surface water and groundwater - Charles J. B. Gowing; James M. Dinsley; Elizabeth L. Gallannaugh; Pauline L. Smedley; Andrew L. Marriott; Michael J. Bowes; Kay A. Green; Michael J. Watts (Environmental Geochemistry and Health, 2020)

Use of pre-industrial baselines to monitor anthropogenic enrichment of metals concentrations in recently deposited sediment of floodplain lakes in the Peace-Athabasca Delta (Alberta, Canada) - Tanner J. Owca; Mitchell L. Kay; Jelle Faber; Casey R. Remmer; Nelson Zabel; Johan A. Wiklund; Brent B. Wolfe; Roland I. Hall (Environmental Monitoring and Assessment, 2020)
Well-designed monitoring approaches are needed to assess effects of industrial development on downstream aquatic environments and guide environmental stewardship. Here, we develop and apply a monitoring approach to detect potential enrichment of metals concentrations in surficial lake sediments of the Peace-Athabasca Delta (PAD), northern Alberta, Canada. Since the ecological integrity of the PAD is strongly tied to river floodwaters that replenish lakes in the delta, and the PAD is located downstream of the Alberta oil sands, concerns have been raised over the potential transport of industry-supplied metals to the PAD via the Athabasca River. Surface sediment samples were collected in September 2017 from 61 lakes across the delta, and again in July 2018 from 20 of the same lakes that had received river floodwaters 2 months earlier, to provide snapshots of metals concentrations (Be, Cd, Cr, Cu, Ni, Pb, V, and Zn) that have recently accumulated in these lakes. To assess for anthropogenic enrichment, surficial sediment metals concentrations were normalized to aluminum and compared to pre-industrial baseline (i.e., reference) metal-aluminum linear relations for the Athabasca and Peace sectors of the PAD developed from pre-1920 measurements in lake sediment cores. Numerical analysis demonstrates no marked enrichment of these metals concentrations above pre-1920 baselines despite strong ability (> 99% power) to detect enrichment of 10%. Measurements of river sediment collected by the Regional Aquatics- and Oil Sands-Monitoring Programs (RAMP/OSM) also did not exceed pre-1920 concentrations. Thus, results presented here show no evidence of substantial oil sands-derived metals enrichment of sediment supplied by the Athabasca River to lakes in the PAD and demonstrate the usefulness of these methods as a monitoring framework.

Global fern and lycophyte richness explained: How regional and local factors shape plot richness - Anna Weigand; Stefan Abrahamczyk; Isabelle Aubin; Claudia Bita‐Nicolae; Helge Bruelheide; Cesar I. Carvajal‐Hernández; Daniele Cicuzza; Lucas Erickson Nascimento da Costa; János Csiky; Jürgen Dengler; André Luís de Gasper; Greg R. Guerin; et al. (Journal of Biogeography, 2020)
Aim To disentangle the influence of environmental factors at different spatial grains (regional and local) on fern and lycophyte species richness and to ask how regional and plot‐level richness are related to each other. Location Global. Taxon Ferns and lycophytes. Methods We explored fern and lycophyte species richness at two spatial grains, regional (hexagonal grid cells of 7,666 km 2 ) and plot level (300–500 m 2 ), in relation to environmental data at regional and local grains (the 7,666 km 2 hexagonal grid cells and 4 km 2 square grid cells, respectively). For the regional grain, we obtained species richness data for 1,243 spatial units and used them together with climatic and topographical predictors to model global fern richness. For the plot‐level grain, we collated a global dataset of nearly 83,000 vegetation plots with a surface area in the range 300–500 m 2 in which all fern and lycophyte species had been counted. We used structural equation modelling to identify which regional and local factors have the biggest effect on plot‐level fern and lycophyte species richness worldwide. We investigate how plot‐level richness is related to modelled regional richness at the plot's location. Results Plot‐level fern and lycophyte species richness were best explained by models allowing a link between regional environment and plot‐level richness. A link between regional richness and plot‐level richness was essential, as models without it were rejected, while models without the regional environment‐plot‐level richness link were still valid but had a worse goodness‐of‐fit value. Plot‐level richness showed a hump‐shaped relationship with regional richness. Main conclusions Regional environment and regional fern and lycophyte species richness each are important determinants of plot‐level richness, and the inclusion of one does not substitute the inclusion of the other. Plot‐level richness increases with regional richness until a saturation point is reached, after which plot‐level richness decreases despite increasing regional richness, possibly reflecting species interactions.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

From Observation to Information and Users: The Copernicus Marine Service Perspective - Pierre Yves Le Traon; Antonio Reppucci; Enrique Alvarez Fanjul; Lotfi Aouf; Arno Behrens; Maria Belmonte; Abderrahim Bentamy; Laurent Bertino; Vittorio Ernesto Brando; Matilde Brandt Kreiner; Mounir Benkiran; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

National-scale analysis of low flow frequency: historical trends and potential future changes - A. L. Kay; V. A. Bell; B. P. Guillod; R. G. Jones; A. C. Rudd (Climatic Change, 2018)

Interrogating marine virus‐host interactions and elemental transfer with BONCAT and nanoSIMS‐based methods - Alexis L. Pasulka; Kimberlee Thamatrakoln; Sebastian H. Kopf; Yunbin Guan; Bonnie Poulos; Annie Moradian; Michael J. Sweredoski; Sonja Hess; Mathew B. Sullivan; Kay D. Bidle; Victoria J. Orphan (Environmental Microbiology, 2018)
Summary While the collective impact of marine viruses has become more apparent over the last decade, a deeper understanding of virus‐host dynamics and the role of viruses in nutrient cycling would benefit from direct observations at the single‐virus level. We describe two new complementary approaches – stable isotope probing coupled with nanoscale secondary ion mass spectrometry (nanoSIMS) and fluorescence‐based biorthogonal non‐canonical amino acid tagging (BONCAT) – for studying the activity and biogeochemical influence of marine viruses. These tools were developed and tested using several ecologically relevant model systems ( Emiliania huxleyi /EhV207, Synechococcus sp . WH8101/Syn1 and Escherichia coli /T7). By resolving carbon and nitrogen enrichment in viral particles, we demonstrate the power of nanoSIMS tracer experiments in obtaining quantitative estimates for the total number of viruses produced directly from a particular production pathway (by isotopically labelling host substrates). Additionally, we show through laboratory experiments and a pilot field study that BONCAT can be used to directly quantify viral production (via epifluorescence microscopy) with minor sample manipulation and no dependency on conversion factors. This technique can also be used to detect newly synthesized viral proteins. Together these tools will help fill critical gaps in our understanding of the biogeochemical impact of viruses in the ocean.

Local Government Capacity to Respond to Environmental Change: Insights from Towns in New York State - Lincoln R. Larson; T. Bruce Lauber; David L. Kay; Bethany B. Cutts (Environmental Management, 2017)

High‐resolution sequencing reveals unexplored archaeal diversity in freshwater wetland soils - Adrienne B. Narrowe; Jordan C. Angle; Rebecca A. Daly; Kay C. Stefanik; Kelly C. Wrighton; Christopher S. Miller (Environmental Microbiology, 2017)
Summary Despite being key contributors to biogeochemical processes, archaea are frequently outnumbered by bacteria, and consequently are underrepresented in combined molecular surveys. Here, we demonstrate an approach to concurrently survey the archaea alongside the bacteria with high‐resolution 16S rRNA gene sequencing, linking these community data to geochemical parameters. We applied this integrated analysis to hydric soils sampled across a model methane‐emitting freshwater wetland. Geochemical profiles, archaeal communities, and bacterial communities were independently correlated with soil depth and water cover. Centimeters of soil depth and corresponding geochemical shifts consistently affected microbial community structure more than hundreds of meters of lateral distance. Methanogens with diverse metabolisms were detected across the wetland, but displayed surprising OTU‐level partitioning by depth. Candidatus Methanoperedens spp. archaea thought to perform anaerobic oxidation of methane linked to iron reduction were abundant. Domain‐specific sequencing also revealed unexpectedly diverse non‐methane‐cycling archaeal members. OTUs within the underexplored Woesearchaeota and Bathyarchaeota were prevalent across the wetland, with subgroups and individual OTUs exhibiting distinct occupancy and abundance distributions aligned with environmental gradients. This study adds to our understanding of ecological range for key archaeal taxa in a model freshwater wetland, and links these taxa and individual OTUs to hypotheses about processes governing biogeochemical cycling.

Effects of past and present livestock grazing on herpetofauna in a landscape‐scale experiment - Geoffrey M. Kay; Alessio Mortelliti; Ayesha Tulloch; Philip Barton; Daniel Florance; Saul A. Cunningham; David B. Lindenmayer (Conservation Biology, 2017)
Livestock grazing is the most widespread land use on Earth and can have negative effects on biodiversity. Yet, many of the mechanisms by which grazing leads to changes in biodiversity remain unresolved. One reason is that conventional grazing studies often target broad treatments rather than specific parameters of grazing (e.g., intensity, duration, and frequency) or fail to account for historical grazing effects. We conducted a landscape‐scale replicated grazing experiment (15,000 km 2 , 97 sites) to examine the impact of past grazing management and current grazing regimes (intensity, duration, and frequency) on a community of ground‐dwelling herpetofauna (39 species). We analyzed community variables (species richness and composition) for all species and built multiseason patch‐occupancy models to predict local colonization and extinction for the 7 most abundant species. Past grazing practices did not influence community richness but did affect community composition and patch colonization and extinction for 4 of 7 species. Present grazing parameters did not influence community richness or composition, but 6 of the 7 target species were affected by at least one grazing parameter. Grazing frequency had the most consistent influence, positively affecting 3 of 7 species (increased colonization or decreased extinction). Past grazing practice affected community composition and population dynamics in some species in different ways, which suggests that conservation planners should examine the different grazing histories of an area. Species responded differently to specific current grazing practices; thus, incentive programs that apply a diversity of approaches rather than focusing on a change such as reduced grazing intensity should be considered. Based on our findings, we suggest that determining fine‐scale grazing attributes is essential for advancing grazing as a conservation strategy.

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

The basis function approach for modeling autocorrelation in ecological data - Trevor J. Hefley; Kristin M. Broms; Brian M. Brost; Frances E. Buderman; Shannon L. Kay; Henry R. Scharf; John R. Tipton; Perry J. Williams; Mevin B. Hooten (Ecology, 2017)
Analyzing ecological data often requires modeling the autocorrelation created by spatial and temporal processes. Many seemingly disparate statistical methods used to account for autocorrelation can be expressed as regression models that include basis functions. Basis functions also enable ecologists to modify a wide range of existing ecological models in order to account for autocorrelation, which can improve inference and predictive accuracy. Furthermore, understanding the properties of basis functions is essential for evaluating the fit of spatial or time‐series models, detecting a hidden form of collinearity, and analyzing large data sets. We present important concepts and properties related to basis functions and illustrate several tools and techniques ecologists can use when modeling autocorrelation in ecological data.

Evaluation of current and projected Antarctic precipitation in CMIP5 models - Cyril Palerme; Christophe Genthon; Chantal Claud; Jennifer E. Kay; Norman B. Wood; Tristan L’Ecuyer (Climate Dynamics, 2017)

Solutions for ecosystem‐level protection of ocean systems under climate change - Ana M. Queirós; Klaus B. Huebert; Friedemann Keyl; Jose A. Fernandes; Willem Stolte; Marie Maar; Susan Kay; Miranda C. Jones; Katell G. Hamon; Gerrit Hendriksen; Youen Vermard; Paul Marchal; et al. (Global Change Biology, 2016)
The Paris Conference of Parties ( COP 21) agreement renewed momentum for action against climate change, creating the space for solutions for conservation of the ocean addressing two of its largest threats: climate change and ocean acidification ( CCOA ). Recent arguments that ocean policies disregard a mature conservation research field and that protected areas cannot address climate change may be oversimplistic at this time when dynamic solutions for the management of changing oceans are needed. We propose a novel approach, based on spatial meta‐analysis of climate impact models, to improve the positioning of marine protected areas to limit CCOA impacts. We do this by estimating the vulnerability of ocean ecosystems to CCOA in a spatially explicit manner and then co‐mapping human activities such as the placement of renewable energy developments and the distribution of marine protected areas. We test this approach in the NE Atlantic considering also how CCOA impacts the base of the food web which supports protected species, an aspect often neglected in conservation studies. We found that, in this case, current regional conservation plans protect areas with low ecosystem‐level vulnerability to CCOA , but disregard how species may redistribute to new, suitable and productive habitats. Under current plans, these areas remain open to commercial extraction and other uses. Here, and worldwide, ocean conservation strategies under CCOA must recognize the long‐term importance of these habitat refuges, and studies such as this one are needed to identify them. Protecting these areas creates adaptive, climate‐ready and ecosystem‐level policy options for conservation, suitable for changing oceans.

BCL2 protein signalling determines acute responses to neoadjuvant chemoradiotherapy in rectal cancer - L. Flanagan; A. U. Lindner; C. de Chaumont; J. Kehoe; J. Fay; O. Bacon; S. Toomey; H. J. Huber; B. T. Hennessy; E. W. Kay; D. A. McNamara; J. H. M. Prehn (Journal of Molecular Medicine, 2015)

Novel molecular determinants of viral susceptibility and resistance in the lipidome of E miliania huxleyi - James M. Fulton; Helen F. Fredricks; Kay D. Bidle; Assaf Vardi; B. Jacob Kendrick; Giacomo R. DiTullio; Benjamin A. S. Van Mooy (Environmental Microbiology, 2014)
Summary Viruses play a key role in controlling the population dynamics of algae, including E miliania huxleyi , a globally distributed haptophyte with calcite coccoliths that comprise ca. 50% of the sinking carbonate flux from the surface ocean. E miliania huxleyi viruses ( EhVs ) routinely infect and terminate E . huxleyi blooms. EhVs are surrounded by a lipid envelope, which we found to be comprised largely of glycosphingolipids ( GSLs ) with lesser amounts of polar glycerolipids. Infection appears to involve membrane fusion between the virus and host, and we hypothesized that specific polar lipids may facilitate virus attachment. We identified three novel intact polar lipids in E . huxleyi strain CCMP 374 and EhV 86, including a GSL with a monosaccharide sialic acid headgroup ( sGSL ); for all 11 E . huxleyi strains we tested, there was a direct relationship between sGSL content and sensitivity to infection by EhV 1, EhV 86 and EhV 163. In mesocosms, the E . huxleyi population with greatest initial sGSL content had the highest rate of virus‐induced mortality. We propose potential physiological roles for sGSL that would be beneficial for growth but leave cells susceptible to infection, thus furthering the discussion of R ed Q ueen‐based co‐evolution and the cost(s) of sensitivity and resistance in the dynamic E . huxleyi ‐ EhV system.

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Profiling drug-induced cell death pathways in the zebrafish lateral line - Allison B. Coffin; Kay L. Williamson; Anna Mamiya; David W. Raible; Edwin W. Rubel (Apoptosis, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Sequence Analysis of 5′ Regulatory Regions of the Machado–Joseph Disease Gene (ATXN3) - Conceição Bettencourt; Mafalda Raposo; Nadiya Kazachkova; Cristina Santos; Teresa Kay; João Vasconcelos; Patrícia Maciel; Karina C. Donis; Maria Luiza Saraiva-Pereira; Laura B. Jardim; Jorge Sequeiros; Jácome Bruges-Armas; et al. (The Cerebellum, 2012)

Effects of mu opioid receptor antagonism on cognition in obese binge-eating individuals - Samuel R. Chamberlain; Karin Mogg; Brendan P. Bradley; Annelize Koch; Chris M. Dodds; Wenli X. Tao; Kay Maltby; Bhopinder Sarai; Antonella Napolitano; Duncan B. Richards; Edward T. Bullmore; Pradeep J. Nathan (Psychopharmacology, 2012)

Nprl3 is required for normal development of the cardiovascular system - Monika S. Kowalczyk; Jim R. Hughes; Christian Babbs; Luis Sanchez-Pulido; Dorota Szumska; Jacqueline A. Sharpe; Jacqueline A. Sloane-Stanley; Gillian M. Morriss-Kay; Leslie B. Smoot; Amy E. Roberts; Hugh Watkins; Shoumo Bhattacharya; et al. (Mammalian Genome, 2012)

Reproductive success of three passerine species exposed to dioxin-like compounds near Midland, Michigan, USA - Timothy B. Fredricks; Matthew J. Zwiernik; Rita M. Seston; Sarah J. Coefield; Cassandra N. Glaspie; Dustin L. Tazelaar; Denise P. Kay; John L. Newsted; John P. Giesy (Ecotoxicology, 2012)

Predicting Capacity Demand on Sanctuaries for African Chimpanzees (Pan troglodytes) - Lisa J. Faust; Doug Cress; Kay H. Farmer; Stephen R. Ross; Benjamin B. Beck (International Journal of Primatology, 2011)

Menopausal hormone therapy and risk of ovarian cancer in the European prospective investigation into cancer and nutrition - Konstantinos K. Tsilidis; Naomi E. Allen; Timothy J. Key; Laure Dossus; Rudolf Kaaks; Kjersti Bakken; Eiliv Lund; Agnès Fournier; Christina C. Dahm; Kim Overvad; Louise Hansen; Anne Tjønneland; et al. (Cancer Causes & Control, 2011)

Candidate Screening of the TRPC3 Gene in Cerebellar Ataxia - Esther B. E. Becker; Brent L. Fogel; Sanjeev Rajakulendran; Anna Dulneva; Michael G. Hanna; Susan L. Perlman; Daniel H. Geschwind; Kay E. Davies (The Cerebellum, 2011)

Enzymatic Characterisation of USP7 Deubiquitinating activity and Inhibition - Jonathan D. Wrigley; Kay Eckersley; Ian M. Hardern; Lindsey Millard; Michael Walters; Stephen W. Peters; Richard Mott; Thorsten Nowak; Richard A. Ward; Peter B. Simpson; Kevin Hudson (Cell Biochemistry and Biophysics, 2011)

In vitro and in vivo characterisation of a novel c-FLIP-targeted antisense phosphorothioate oligonucleotide - Andrew E. Logan; Timothy R. Wilson; Catherine Fenning; Rob Cummins; Elaine Kay; Patrick G. Johnston; Daniel B. Longley (Apoptosis, 2010)

Passerine Exposure to Primarily PCDFs and PCDDs in the River Floodplains Near Midland, Michigan, USA - Timothy B. Fredricks; Matthew J. Zwiernik; Rita M. Seston; Sarah J. Coefield; Stephanie C. Plautz; Dustin L. Tazelaar; Melissa S. Shotwell; Patrick W. Bradley; Denise P. Kay; John P. Giesy (Archives of Environmental Contamination and Toxicology, 2010)

Hepatic P450 Enzyme Activity, Tissue Morphology and Histology of Mink (Mustela vison) Exposed to Polychlorinated Dibenzofurans - Jeremy N. Moore; John L. Newsted; Markus Hecker; Matthew J. Zwiernik; Scott D. Fitzgerald; Denise P. Kay; Xiaowei Zhang; Eric B. Higley; Lesa L. Aylward; Kerrie J. Beckett; Robert A. Budinsky; Steven J. Bursian; et al. (Archives of Environmental Contamination and Toxicology, 2009)

Ethanol intake and the risk of pancreatic cancer in the European prospective investigation into cancer and nutrition (EPIC) - Sabine Rohrmann; Jakob Linseisen; Alina Vrieling; Paolo Boffetta; Rachael Z. Stolzenberg-Solomon; Albert B. Lowenfels; Majken K. Jensen; Kim Overvad; Anja Olsen; Anne Tjonneland; Marie-Christine Boutron-Ruault; Francoise Clavel-Chapelon; et al. (Cancer Causes & Control, 2009)

Presence and metabolism of endogenous androgenic–anabolic steroid hormones in meat-producing animals: a review - J. Scarth; C. Akre; L. van Ginkel; B. Le Bizec; H. De Brabander; W. Korth; J. Points; P. Teale; J. Kay (Food Additives & Contaminants: Part A, 2009)

Stoichiometric response of nitrogen-fixing and non-fixing dicots to manipulations of CO2, nitrogen, and diversity - Amy M. Novotny; John D. Schade; Sarah E. Hobbie; Adam D. Kay; Marcia Kyle; Peter B. Reich; James J. Elser (Oecologia, 2007)

Neuromelanin and its interaction with iron as a potential risk factor for dopaminergic neurodegeneration underlying Parkinson's disease - Manfred Gerlach; Kay L. Double; Dorit Ben-Shachar; Luigi Zecca; Moussa B. H. Youdim; Peter Riederer (Neurotoxicity Research, 2003)

Strategies for the protection of dopaminergic neurons against neurotoxicity - Manfred Gerlach; Kay L. Double; Moussa B. H. Youdim; Peter Riederer (Neurotoxicity Research, 2000)

Effects of Measurement Error and Sampling Resolution on Estimates of Atrial Tissue Recovery Parameters - M. W. Kay; P. V. Bayly; R. B. Schuessler (Annals of Biomedical Engineering, 2000)

Anti-T cell strategies in asthma - O. M. Kon; A. B. Kay (Inflammation Research, 1999)

Functional studies on the anti-pathoangiogenic properties of CM101 - He-Ping Yan; Clint E. Carter; En-ze Wang; David L. Page; Kay Washington; Barbara D. Wamil; F. Michael Yakes; Gary B. Thurman; Carl G. Hellerqvist (Angiogenesis, 1998)

Isolation and characterization of dengue viruses serotype 1 from an epidemic in northern Queensland, Australia - J. Blok; B. H. Kay; R. A. Hall; B. M. Gorman (Archives of Virology, 1988)

Pleiotropic effect of the gene hairless on hepatotoxicity of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin in mice - J. B. Greig; J. E. Francis; S. J. E. Kay; T. Lister; D. E. Ray; A. A. Seawright; A. G. Smith (Archives of Toxicology, 1987)